Features of the development of mediation in the Republic of Kazakhstan: a comparative legal analysis - Kalshabaeva, М.Zh.; Sartaev, S.А.; Abdykadyr, U. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
Mediation is an alternative method of dispute resolution that is neutral, does not represent the interests of the parties in resolving the dispute, involves a third party-a mediator who helps the parties reach a certain agreement on the dispute, and the parties have full control over the processes of decision – making and the requirements for its resolution. It is also important to note that there are no exceptions to this rule. The article discusses the development of the Institute of Mediation in Kazakhstan as an alternative method of dispute resolution. Due to the lack of proper development of the Institute of Mediation, the opinions of scientists and lawyers will be analyzed, and the factors hindering the development of mediation in Kazakhstan will be identified by comparing the experience of China, Germany, Georgia, and Singapore in implementing and developing alternative dispute resolution methods. In order to distinguish these points, a review and comparative analysis of the scientific works of scientists studying the Institute of Mediation, laws and scientific works of a number of foreign countries on mediation was conducted. The methodological basis of the article is analysis, synthesis, comparative-legal, logical-legal, historical, and statistical methods.